Evaluation of a new PT‐INR monitoring system in patients with the antiphospholipid syndrome. (20th June 2016) - Braham, S.; Novembrino, C.; Moia, M.; Torresani, E.; Tripodi, A.
Summary: Introduction: Patients on anticoagulant therapy with vitamin K antagonists (VKA) need frequent INR monitoring. Reliability of point‐of‐care (POC) devices for measuring INR needs rigorous evaluation, particularly in patient with the antiphospholipid syndrome (APS). The aim of this study was to evaluate the accuracy of the ProTime InRhythm ™ System (here called device) for INR measurement in patients with APS on VKA. Methods: We compared the device INR vs . the laboratory INR measurement for blood samples from 29 APS‐positive and 31 APS‐negative patients consecutively enrolled. APS was confirmed by positive serological and/or phospholipid‐dependent coagulation tests. Chromogenic factor X assay was used to evaluate anticoagulation. Bland–Altman difference plot for paired INR (POC vs . laboratory) was used to evaluate agreement between the device and the laboratory. The device INR relationship with factor X chromogenic assay was evaluated by orthogonal regression analysis. Results: Overall, 97% of the device INR measurements were similar to laboratory INR values with an absolute difference less than 0.4 units. Correlation coefficient for the device INR vs . factor X was −0.69 ( P < 0.0001, CI 95% −0.80 to −0.52). Conclusions: The ProTime InRhythm System ™ is an accurate point‐of‐care device for measuring INR also in patients with and without APS.